Effects of transmembrane pressure on the performance of flat sheet membrane on milk protein separation. - Kasman, Mokhtar (2009)
This research is to study the effect of transmembrane pressure on cross flow filtration on protein milk separation. The different transmembrane pressure will be effect the performance of cross flow filtration. By this research, the optimum operation condition of the cross flow filtration will get especially when comes to protein milk separation. In other word, the suitable parameter will be known in order to separate protein milk. Protein milk can be separated from other composition in the skim milk using cross flow filtration. Before using filtration, skim milk should be centrifuged to remove fat and undesired composition to reduce membrane faultiness or membrane blockage. Protein compositions in both permeate and retentate analyzed using Lowry method. From the result, the optimum operation condition for milk protein separation is at TMP 25 psi and flux recorded is 94 ml/ (m2.min) and 78 ml/ (m2.min). This is experiment using 10K membrane cassette in batch mode.